Organization commitment in a workplace at Petronas Dagangan Berhad / Nur ‘Atiqah Mohd Taib and Fazreen Kamsudin - Mohd Taib, Nur ‘Atiqah; Kamsudin, Fazreen (Faculty of Business and Management, 2016)
Organizational commitment (OC) is one of the most fundamental concepts that has been explored in relation to workforce motivation and productivity. Its importance in any organization cannot be underrated. It is believed that employees with strong organizational will work harder in order to contribute to organization’s performance. It is also a psychological state that binds an employee to an organization, and the Three-Component Model of organizational commitment (Meyer & Allen, 1991) posits that employees bind with their organizations as a result of desire (affective commitment), need (continuance commitment) and obligation (normative commitment). Similarly, relationship commitment between two people also has been conceived as a psychological state (Rusbult & Buunk, 1993), and Arriaga and Agnew (2001) outlined affective, cognitive and conative components of the state. This exploratory study examined the relationship between these conceptually parallel commitment models by determining how the dimensions of the three types of commitment correlate with one another. Data collected from 121 working adults at Petronas.